Penerapan Model Pembelajaran Berbasis Proyek Pada Sekolah Inklusi Di Paud Inklusi Melati Budi Insani - Lania Rizka Salam; Rr. Dina Kusuma Wardhani; Fadlullah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose os this study was to find out specifically the implementation of a project-based learning model at the Melati Budi Insani Inclusive Early Childhood. The method used in this study is qualitative with a descriptive approach. The research was conducted at the Melati Budi Insani Inclusive PAUD in November 2025. The population and sample in this study included one class teacher and nine students in the Gajah class aged 6-7 years. The findings showed that project-based learning was planned by considering learning themes, students' needs, and students' abilities. The implementation was carried out through activities related to students' daily lives, with the teacher acting as a facilitator and guide. However, the participation of students with special needs was not yet optimal and still required more intensive assistance. Learning evaluation was conducted continuously through observation, students' work, daily records, activity monitoring, and feedback. It can be concluded that the implementation of project-based learning at PAUD Inklusi Melati Budi Insani has been carried out fairly well in accordance with the characteristics of inclusive education, although improvements are still needed in addressing individual students' needs and implementing learning reflection activities.